x percent of y percent of z is decreased by y percent

Making the statement more mathematical friendly

x% of y% of z is decreased by y%

x% of

(y% of z) is decreased by y%

\((x% of \frac{yz}{100})\) is decreased by y%

\(\frac{xyz}{100 * 100}\) is decreased by y%

\(\frac{xyz}{100*100} - \frac{xy^2z}{100*100*100}\)

\(\frac{100xyz - xy^2z}{100*100*100}\)

Answer = A

Small Tip:Number of times you see the % sign (2 zero's), those number of zero's in the denominator

\(a%b = \frac{ab}{10^2}\)

\(a%b%c = \frac{abc}{10000}\)

\(a%b%c%d = \frac{abcd}{10^6}\)

\(a%b%c%d......... n = \frac{abcd......n}{10^{(n-1)}}\)

_________________

Kindly press "+1 Kudos" to appreciate